Availability of Adequately Iodized Salt at Household Level and Associated Factors in Dire Dawa, Eastern Ethiopia - Anteneh Berhane Yaye; Negga Baraki; Birhanu Seyum Endale (International Journal of Public Health Science (IJPHS), 2016)
In Ethiopia, Iodine Deficiency Disorder has been recognized as a serious public health problem for the past six decades. In 2011, an estimated 12 million school-age children were living with inadequate iodine, and 66 million people were at risk of iodine deficiency. One out of every 1000 people is a cretin mentally handicapped, due to a congenital thyroid deficiency, and about 50000 prenatal deaths are occurring annually due to iodine deficiency disorders. Only 5.7% of the households were using iodized salt in Dire Dawa city Administration, which is below the legal requirement.This study assessed availability of adequately iodized salt at household level and associated factors in Dire Dawa town, East Ethiopia. Community based cross-sectional study was carried out among households in Dire Dawa town during March 16-26, 2015. Multistage sampling technique was used. Data were collected using a pretested and structured questionnaire by a face-to-face interview technique. Bivariate and multivariate analyses were performed to check associations and control confounding. A total of 694 participants were participated. The availability of adequately iodized salt (≥15 parts per million) in the study area was 7.5% (95% CI; 5.6-9.5). Multivariate result showed that health information about iodized salt (AOR=8.96, 95% CI; 4.68-17.16) (p=0.03), good knowledge about iodized salt (AOR=9.23, 95% CI; 3.34-25.5) (p=0.01) and using packed salt (AOR=3.99, 95% CI; 1.48-10.73) (p=0.006) were associated with availability of adequately iodized salt at household level. Availability of adequately iodized salt at household level was very low.  Hence, households should be sensitized about importance of iodized salt and its proper handling at the household level.